Association of Serum Uric Acid with Preeclampsia: A Case Control Study (Delta Medical College Journal, 2013)
Background: Preeclampsia (PE) is still one of the important causes of maternal and fetal mortality in Bangladesh. Many researches have been done to identify a unique screening test that would predict the risk of developing PE before the classic symptoms appear. One of the most accessible and easiest screening tests is serum uric acid measurement. Numerous studies have demonstrated a relation between elevated maternal serum uric acid levels and adverse maternal and fetal outcome. Among several pathophysiologic factors the most commonly accepted explanation for hyperuricemia in PE is increased reabsorption and decreased excretion of uric acid. Objective: The aim of the present study was to assess the association of serum uric acid with preeclampsia. Materials and method: A case control study was conducted in the department of Biochemistry, Dhaka Medical College, Dhaka from July 2010 to June 2011. A total number of 100 pregnant women in third trimester of pregnancy attending in Obstetrics and Gynaecology department of Dhaka Medical College Hospital were selected purposively as study subjects. Among them 50 pregnant women with preeclampsia were selected as cases and 50 normal healthy pregnant women as controls. Results: Most of the study subjects were within 21 30 years of age group and mean age in case and control was 24.06±3.71 and 24.66±3.22 years respectively, which was not statistically different. Mean gestational age in case and control was 33.50±2.55 weeks and 33.60±2.95 weeks respectively, which was also not statistically different. Among the study subjects majority was primi in both groups (case 76%, contol 58%) showing no statistical significance. Majority of the subjects in both groups were irregular in their antenatal checkup (case 52%, contol 40%). Uric acid concentration was measured in all the study subjects. The mean serum uric acid concentration in cases and controls were 7.01±1.90 mg/dl and 4.55±1.63 mg/dl respectively. This difference was highly significant in statistical point of view. Conclusion: Hyperuricemia is associated with preeclampsia. DOI: http://dx.doi.org/10.3329/dmcj.v1i2.15918 Delta Med Col J. Jul 2013;1(2):46-50